Implementasi Pembelajaran Berdiferensiasi dan Dampaknya pada Hasil Belajar Siswa: Studi Kasus di SD Sebuku - Eka Supriyanti; Woro Sri Hastuti; Fery Muhammad Firdaus (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This study aims to analyze the implementation of differentiated instruction (DI) at SDN 005 Sebuku, an elementary school in the 4T (Frontier, Outermost, Disadvantaged, and Transmigration) region, and to identify the inhibiting factors and their impact on student learning outcomes. This school faces significant challenges in the form of limited learning facilities and infrastructure, limited internet access, diversity in cultural backgrounds and student readiness to learn, and a lack of training opportunities for teachers. This study uses a qualitative approach with an intrinsic case study design, involving the principal, teachers, and students as key informants, and is supported by documents such as lesson plans, grade data, and initial assessment results. Data collection techniques included in-depth interviews, observation of the learning process in the classroom, and documentation studies, while data analysis was conducted using the Miles et al. model through the stages of data reduction, data presentation, and data verification. The results showed that the implementation of DI at SDN 005 Sebuku was able to increase student motivation, engagement, and learning outcomes, despite facing obstacles such as time constraints, learning facilities, and student heterogeneity. In conclusion, the implementation of DI had a positive impact on students' academic scores, motivation, engagement, and self-confidence, although the results were not yet uniform. Therefore, this strategy is worth developing in schools to address the challenges of 4T schools and requires continuous support from teachers, principals, and the government. This research can serve as a basis for more inclusive and adaptive learning practices in remote areas.